“Talleres de artes escènicas para el desarrollo del lenguaje en Educaciòn Inicial” - Tipanluisa Arequipa, Sandra Nataly (2024)
The present proposal focuses on conducting "Performing Arts Workshops with Didactic Resources for Language Development in Children from the Tingo la Esperanza Parish of Pujilí Canton." It is aimed at supporting the teacher's process through play-based learning, implementing dramatizations, storytelling, puppetry, among other activities, thus promoting both individual and group participation. The primary objective of this project is to propose didactic and innovative workshops. For the development of the proposal, the methodology of the holistic approach was implemented, which allows the child to develop all their intellectual, emotional, and physical abilities. The workshops with didactic resources have been designed to contribute to the educational process with playful activities, so that teachers can implement them during the training of children, fostering basic communication and expression skills for comprehensive human development. Validation by experts and users has been important for the approval of the proposal, as their years of experience have provided reliability, effectiveness, and importance to be put into practice within the classroom process. It has been concluded that the implementation of different didactic resources through playful workshops is of great significance within the educational process, helping to strengthen language development by facilitating bidirectional communication to acquire meaningful learning from a very early age, reinforcing learning through play as an essential strategy.